2010
DOI: 10.1017/s1138741600003735
|View full text |Cite
|
Sign up to set email alerts
|

Teachers' Attitudes and Beliefs about Homosexuality

Abstract: Schools play a key role in transmitting attitudes towards sexual diversity. Many studies stress the importance of teachers' and other professionals' attitudes towards gay men and/or lesbian women. This study evaluates attitudes and prejudices toward homosexuality in a sample of 254 elementary and high school teachers in Barcelona and its surrounding area. The results obtained using a scale of overt and subtle prejudice and a scale of perceived discrepancy of values indicate that discrepancy between likely beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 37 publications
(61 reference statements)
1
7
0
3
Order By: Relevance
“…Among those who did not complete the "Human Sexuality" course, no change was visible in the three research variables. The relation found in this study between level of religiosity and extent of progressiveness in attitudes towards sexuality, is similar to that found in other studies in Israel [13] and in other countries [18,36,37,12,14,38]. These studies found that people who defined themselves as secular possessed more progressive attitudes than people who defined themselves as traditional or religious.…”
Section: Discussionsupporting
confidence: 89%
“…Among those who did not complete the "Human Sexuality" course, no change was visible in the three research variables. The relation found in this study between level of religiosity and extent of progressiveness in attitudes towards sexuality, is similar to that found in other studies in Israel [13] and in other countries [18,36,37,12,14,38]. These studies found that people who defined themselves as secular possessed more progressive attitudes than people who defined themselves as traditional or religious.…”
Section: Discussionsupporting
confidence: 89%
“…These results indicate that students are less informed about homosexuality and suggest that negative attitudes and beliefs about homosexuality exist and are strong. 1 , 2 , 5 , 6 , 9 , 11 , 13 , 15 , 32 …”
Section: Discussionmentioning
confidence: 99%
“…Some of the negative attitudes about homosexuality are influenced by lack of exposure to diversity, 9 religious beliefs, 1 , 2 , 5 , 10 and the social–cultural contexts. 3 , 5 , 11 It appears that having a close contact with a lesbian or gay person increases positive attitudes and reduces prejudicial behaviors toward nonheterosexual individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the gaps identified above related to these key populations, this review highlighted the opportunity for increased standardization across settings in measurement and methodologically sound validation. Given heightened interest in the well-being of key populations around the world, there has been translation – and some validation – of stigma scales in different linguistic contexts, including Chinese [ 95 103 ], Spanish [ 85 , 104 110 ], Turkish [ 111 115 ], Italian [ 106 , 116 118 ], and Hebrew [ 119 , 120 ]. Although increased stigma measurement across settings is an advance, there has been limited psychometric assessment of stigma metrics in many settings.…”
Section: Discussionmentioning
confidence: 99%